Living in a Region With a Low Level of COVID-19 Infection: Health Belief Toward COVID-19 Vaccination and Intention to Receive a COVID-19 Vaccine in Hong Kong Individuals - Linda Yin-king Lee PhD, RN, RM; Kit-ying Chu; Max Hin-wa Chan; Chloe Tsz-ching Wong; Heidi Po-ying Leung; Issac Chun-wing Chan; Crystal Kit-ying Ng; Rachel Yuen-shan Wong; Angel Lok-ching Pun; Yaki Hoi-ying Ng; Joe Ka-chun Ng (SAGE Publishing, 2022)
Introduction Vaccination is vital for controlling the COVID-19 pandemic. Individuals' vaccination intention is a good predictor of vaccine uptake and is influenced by individuals' health belief toward vaccination. Regions with different levels of pandemic severity may present varying effects. This study aimed to determine the influence of health belief on COVID-19 vaccination intention in a region with a low level of COVID-19 infection. Methods This cross-sectional telephone survey was conducted on a quota sample of 800 adults in Hong Kong before the commencement of the local COVID-19 vaccination program. The Health Belief Model Scale-COVID-19 was developed to assess health belief toward COVID-19 vaccination. The contribution of health belief on explaining intention to receive the COVID-19 vaccine was assessed using logistic regression. Results The subjects demonstrated moderate levels in all aspects of health belief. Only 28.9% of the subjects indicated an intention to receive a COVID-19 vaccine. After controlling for age, educational level, marital status, and high risk status, the logistic regression analysis indicated that perceived benefits of vaccination (OR = 1.615; CI 95%: 1.443-1.807; P < .001), perceived susceptibility to COVID-19 (OR = 1.130; CI 95%: 1.032-1.237; P = .008), cues to action toward vaccination (OR = 1.212; CI 95%: 1.108-1.326; P < .001), and perceived barriers to vaccination (OR = .696; CI 95%: .641-.756; P < .001) were associated with intention to receive a COVID-19 vaccine. Conclusion Vaccination campaigns in regions with good control of the pandemic should promote the benefits of vaccination, emphasizing how it can help individuals regain a sense of normalcy in their daily lives and stop the spread of COVID-19. Although the COVID-19 pandemic affects countries worldwide, this study highlights the importance of adopting specific vaccination promotion strategies for regions with different levels of pandemic severity.